The Instagram and the image of a modern woman: influence and interaction - Baskynbayeva, N.K. (KU Publ., 2021)
Today women became more active in social, political and economic spheres. As a result of the impact of West (US and Europe) and East (Arab countries) women have experienced diverse cultural transformations. Accordingly, their system of values, psychology, behaviour and status has changed. To adapt traditional Kazakh values to new social relations, to place it into the spiritual centre of social life is not only a cultural, philosophical or worldview issue, it also has political significance. And the one who can realize it and to make it viable is a woman, a mother and a grandmother. In order to answer the questions about how a woman has changed, how she looks today, what she wants from life, how she positions herself, we can see her social media. Cyber technologies, which have become an integral part of modern human life, including a new type and level of communication, the impact of social networks on women, the influence on the transformation of the image of a woman, the causes and consequences of high demand for Instagram will be analyzed in this paper.
Инстаграм желісі жəне заманауи əйел образы: ықпалы мен қарым-қатынасы
Инстаграм и образ современной женщины: влияние и взаимосвязь
Keywords: social media; Instagram; internet; woman; the image of a woman; communication; post; stories